[Hibiscus, Queen of Tropical Flowers] - (:unkn) unknown (My University, 2010)
Description on the back of the postcard: "White, red, flame and yellow - the Hibiscus is the queen of tropical flowers." Postcard number C3309.
Colour: Coloured (print); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hibiscus--Trinidad and Tobago; Angiosperms--Trinidad and Tobago; Plants, Ornamental--Trinidad and Tobago